Determinan Kepuasan Nasabah Dalam Menggunakan Mobile-Banking Pada Bank Syariah Indonesia Di Kota Banda Aceh - Ilyas, TM. Syahrizal; Wardah (IAIN Langsa, 2024)
The purpose of this study is to measure and analyze the impact of trust, religiosity, efficiency, and service quality on the satisfaction in using mobile-banking among the customers of Bank Syariah Indonesia (BSI)in Banda Aceh City, Indonesia. Togather the data, the study distributed questionnaires to a 100 selected the BSI customers in the city using a purposive sampling technique. Used a linear regression analysis, the study found that trust, efficiency, and service quality have a significant positive impact on the customer satisfaction in using BSI’ mobile-banking BSI. Meanwhile, the religiosity has in significant effect on the customer satisfaction in using mobile-banking of the BSI These findings show the importance of enhancing trust, efficiency, and service quality to promote satisfaction of the BSI’s customers in using mobile-banking.